Daily life satisfaction in Asia: a cross-national survey in twelve societies - Inogushi, Takashi; Basanez, Miguel; Kubota, Yuichi; Sung, Kyum Cho; Khuekao, Jantima; Krirkgulthorn, Tassanee; Yingrengreung, Siritorn; Chung, Robert; Cheong, Angus Weng Hin; Sandoval, Gerardo A. Jay; Deshmukh, Yashwant; Shaw, Kanyika; et al. (Asian Network for Public Opinion Research (ANPOR), 2014)
Aside from political leaders' popularity rates and the stock exchange index of business firms, ordinary people are highly interested in aspects of daily life, such as housing, income, health, family, food, human relations and work. Cross-national opinion polls on daily-life satisfaction were carried out in Japan, South Korea, Thailand, Hong Kong, Macao, the Philippines, India, Myanmar, Taiwan, China, Malaysia and Pakistan in the fall of 2013 and winter 2014.. The percent difference index (PDI) is formulated as the sum of two positive responses (satisfied and somewhat satisfied) minus the sum of two negative responses (dissatisfied and somewhat dissatisfied). Percent difference indices are given according to society and daily-life aspects. For our analysis to go beneath national average and to go beyond national borders, two lines of analysis are carried out. First, the distance between the level of satisfaction of the top and bottom quartiles is given for each society and according to each of the daily-life aspects. Second, the regional sum of satisfaction of the top quartiles and bottom quartiles are shown crossed by daily-life aspects. In this article we confine ourselves to preliminary comparative description and analysis. More solid and deep comparisons will be carried out by local polling leaders of 12 Asian societies in the succeeding issue of the Asian Journal of Public Opinion Research. Nevertheless, two key threads stand out from these preliminary comparisons. First, social relations (family and human relations) stand out as most satisfied aspects of life in most of twelve societies. Second, the need to go beneath national averages and beyond national borders in analyzing cross-national surveys is confirmed. The comparability and validity of cross-national surveys with varying sampling method and survey mode are briefly discussed toward the end of the article.